2017
DOI: 10.1016/j.jped.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Equations based on anthropometry to predict body fat measured by absorptiometry in schoolchildren and adolescents

Abstract: The equations developed in this study can be used to assess the percentage of body fat of Mexican schoolchildren and adolescents, as they demonstrate greater validity and lower error compared with previously published equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…Further, the method has been applied in the estimation of FM% in diverse ethnic groups such as Caucasians, Latinos, Asians and Africans in 111 countries. Nowadays, however, we suggest that body fat distribution would be better represented by equations that consider other fat deposition sites such as the abdominal region, measured at the waist level, and validated by DXA or MRI as this is likely to have more relevance to the metabolic syndrome, type 2 diabetes and cardiovascular diseases [3739].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the method has been applied in the estimation of FM% in diverse ethnic groups such as Caucasians, Latinos, Asians and Africans in 111 countries. Nowadays, however, we suggest that body fat distribution would be better represented by equations that consider other fat deposition sites such as the abdominal region, measured at the waist level, and validated by DXA or MRI as this is likely to have more relevance to the metabolic syndrome, type 2 diabetes and cardiovascular diseases [3739].…”
Section: Discussionmentioning
confidence: 99%
“…A significant association was found between trunk fat mass and BMI and height in boys; in addition to BMI, this variable also had a significant relationship with weight in girls over 13 years of age and waist circumference in girls under 13 years of age. The literature review showed that BMI and waist circumference had a significant role in predicting fat mass [ 12 , 15 , 16 ]. A cross-sectional study in Brazilian adolescents reported that body circumferences, including waist circumference, had high adjusted coefficients of determination to estimate fat mass in girls [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in Brazilian adolescents reported that body circumferences, including waist circumference, had high adjusted coefficients of determination to estimate fat mass in girls [ 15 ]. Another study in schoolchildren and adolescents found that BMI and waist circumference are among the best predictors of body fat percentage [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, although ANT is a widely used method and scientific publications from this field are numerous, the comparison of body composition results obtained with different regression equations has, surprisingly, not been really extensive; most often, only a single or a limited number [21] of selected anthropometrical methods for body composition assessment were compared with a reference method of choice. The purpose of comparisons was most often to check for the accuracy of selected anthropometric method [35, 36], or to create new, population-specific regression equations [37]. Robič et al [24] performed a comparison of sample-specific and non-specific regression equations for BF calculation in pregnant women and clearly demonstrated that the differences in body composition, as determined with different regression equations (even with those specifically developed for the selected sample), go to the extent that the same subject can easily be (miss)classified into different nutritional categories.…”
Section: Discussionmentioning
confidence: 99%